2000
DOI: 10.1118/1.1288393
|View full text |Cite
|
Sign up to set email alerts
|

Red marrow dosimetry for radiolabeled antibodies that bind to marrow, bone, or blood components

Abstract: Hematologic toxicity limits the radioactivity that may be administered for radiolabeled antibody therapy. This work examines approaches for obtaining biodistribution data and performing dosimetry when the administered antibody is known to bind to a cellular component of blood, bone, or marrow. Marrow dosimetry in this case is more difficult because the kinetics of antibody clearance from the blood cannot be related to the marrow. Several approaches for obtaining antibody kinetics in the marrow are examined and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
47
0
1

Year Published

2002
2002
2018
2018

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 61 publications
(49 citation statements)
references
References 84 publications
1
47
0
1
Order By: Relevance
“…Bone marrow concentrations of blinatumomab following blinatumomab administrations were assumed to be about 30% of that in the plasma based on literature report. 46 The model simulation suggested that following either the priming dose (9 µg/day) or the full dose (28 µg/day), blinatumomab is expected to cause near-complete or complete B cell depletion in blood (Figure 5a). Meanwhile, the model simulation results suggested that blinatumomab would induce incomplete depletion of B cells in bone marrow following the 9 µg/day priming dose, but that blinatumomab will lead to near complete depletion of bone marrow B cells following the 28 µg/day full dose, even at a relatively low baseline E:T ratio (assumed 1: 10 in the current simulation) (Figure 5b).…”
Section: Resultsmentioning
confidence: 99%
“…Bone marrow concentrations of blinatumomab following blinatumomab administrations were assumed to be about 30% of that in the plasma based on literature report. 46 The model simulation suggested that following either the priming dose (9 µg/day) or the full dose (28 µg/day), blinatumomab is expected to cause near-complete or complete B cell depletion in blood (Figure 5a). Meanwhile, the model simulation results suggested that blinatumomab would induce incomplete depletion of B cells in bone marrow following the 9 µg/day priming dose, but that blinatumomab will lead to near complete depletion of bone marrow B cells following the 28 µg/day full dose, even at a relatively low baseline E:T ratio (assumed 1: 10 in the current simulation) (Figure 5b).…”
Section: Resultsmentioning
confidence: 99%
“…For radiopharmaceuticals that bind to marrow tissues or to mineral bone, explicit knowledge of the patient's total and, in some cases, regional active marrow mass is required for proper scaling of radionuclide S values (4), which are in turn assessed in a reference computational phantom or skeletal model (5,6). Under the assumption that no adjustments are required of the radiation-absorbed fraction-fraction of emitted particle energy that is absorbed in the target tissuepatient-specific S values to AM from radiopharmaceuticals localized in skeletal source tissue r S may be estimated as: Eq.…”
mentioning
confidence: 99%
“…The use of a scintigraphic method has the advantage of taking the actual activity in the bone marrow into account. 6 The poor correlation between absorbed dose and hematologic toxicity may partly be due to shortcomings of the dosimetry methods in use. Improved knowledge of activity distribution might improve the correlation.…”
mentioning
confidence: 99%